2005
DOI: 10.1016/j.molcel.2005.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic ADP-Ribose and Hydrogen Peroxide Synergize with ADP-Ribose in the Activation of TRPM2 Channels

Abstract: The melastatin-related transient receptor potential channel TRPM2 is a plasma membrane Ca2+-permeable cation channel that is activated by intracellular adenosine diphosphoribose (ADPR) binding to the channel's enzymatic Nudix domain. Channel activity is also seen with nicotinamide dinucleotide (NAD+) and hydrogen peroxide (H2O2), but their mechanisms of action remain unknown. Here, we identify cyclic adenosine diphosphoribose (cADPR) as an agonist of TRPM2 with dual activity: at concentrations above 100 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
371
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(394 citation statements)
references
References 29 publications
14
371
9
Order By: Relevance
“…A doseresponse fit to the data yielded a half-maximal effective concentration (EC 50 ) for ADPR of 1.1 μM with a Hill coefficient of 1.5. This is considerably lower than the EC 50 values obtained for heterologously expressed TRPM2 in HEK293 cells (10 μM) [7,16], or native TRPM2 in Jurkat T cells (7 μM) [10], U937 monocytes (40 μM) [4], and RINm5f cells (20 μM, Fleig unpublished observations), indicating that both ionic and cellular environment can determine the sensitivity of TRPM2 channels to ADPR. Several cellular systems have been shown to require the presence of intracellular and/or extracellular Ca 2+ to evoke ADPR-induced TRPM2 currents, including human neutrophils [4,12,[14][15][16].…”
Section: Regulation Of Trpm2 By Intracellular Ca 2+mentioning
confidence: 68%
See 3 more Smart Citations
“…A doseresponse fit to the data yielded a half-maximal effective concentration (EC 50 ) for ADPR of 1.1 μM with a Hill coefficient of 1.5. This is considerably lower than the EC 50 values obtained for heterologously expressed TRPM2 in HEK293 cells (10 μM) [7,16], or native TRPM2 in Jurkat T cells (7 μM) [10], U937 monocytes (40 μM) [4], and RINm5f cells (20 μM, Fleig unpublished observations), indicating that both ionic and cellular environment can determine the sensitivity of TRPM2 channels to ADPR. Several cellular systems have been shown to require the presence of intracellular and/or extracellular Ca 2+ to evoke ADPR-induced TRPM2 currents, including human neutrophils [4,12,[14][15][16].…”
Section: Regulation Of Trpm2 By Intracellular Ca 2+mentioning
confidence: 68%
“…We have previously reported that cADPR, H 2 O 2 , and NAADP can synergize with the primary agonist ADPR to more efficiently activate TRPM2 [7] and we recently demonstrated in Jurkat T cells and HEK293 cells overexpressing TRPM2 that intracellular cations can affect the sensitivity of TRPM2 channels to ADPR and cADPR [7,10], which might also affect the synergistic effects of other TRPM2 modulators. Previous studies on TRPM2 in primary neutrophils employed Cs + -based intracellular solutions [12,20], and one study reported the failure of cADPR to activate or synergize with ADPR and AMP to inhibit ADPR-induced TRPM2 currents in human neutrophils [12].…”
Section: Regulation Of Trpm2 By Intracellular Ca 2+mentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, several nucleotide analogues such as adenosine monophosphate (AMP), 8‐bromoadenosine 5′‐diphosphoribose (8‐Br‐ADPR) have also been reported to be TRPM2 inhibitors (Figure 1). 26, 27 Recently, a series of ADPR analogues mainly modified at C‐8 position of purine such as 8‐phenyl‐2′‐ deoxy ‐ADPR (Figure 1) have been shown to potently inhibit TRPM2 current (IC 50  = 3 μ m ) without interfering Ca 2+ release induced by cADPR, NAADP or IP 3 28. Despite the efforts in searching for TRPM2 inhibitors, no TRP‐subtype selective TRPM2 inhibitor has yet been identified.…”
Section: Introductionmentioning
confidence: 99%